Real-world performance of iFIND-TBR for rapid detection of Mycobacterium tuberculosis and rifampicin resistance in China - Ou, Xichao; Zheng, Huiwen; Li, Yan; Zeng, Jiaojian; Huang, Lin; Zhao, Bing; Li, Feina; Xia, Hui; Guo, Yajie; Xing, Ruida; Chen, Yuying; Qin, Zhonghua; et al. (Frontiers in Microbiology, 2026)
ObjectiveTo evaluate the clinical diagnostic ability of iFIND TBR (iFIND) for Mycobacterium tuberculosis (MTB) and resistance to rifampicin (RIF).MethodsSputum samples, prospectively collected from patients with suspected pulmonary tuberculosis between November 2023 and December 2024, were used for comprehensive laboratory testing, including smear microscopy, solid culture, Xpert MTB/RIF, iFIND assays, and proportion method drug susceptibility testing (DST).ResultsAmong the 452 patients, the positive rates of iFIND (80.31%) and Xpert (76.99%) were significantly higher than those of solid culture (65.49%). Based on solid culture as the reference standard, the sensitivity of iFIND for detection of MTB was slightly higher than that of Xpert, but no statistically significant difference was observed (p = 0.157). The sensitivity and specificity of iFIND for detection of MTB were 99.14 and 84.31% relative to the bacteriology reference standard, respectively. Based on the clinical diagnosis results as reference, the higher sensitivity of iFIND than Xpert was observed in detecting MTB (93.46% vs. 90.58%), although the difference was not statistically significant (p = 0.162). The rifampicin detection failure rate was significantly higher in low bacterial load specimens (1+) compared to those with moderate/high loads (≥2+) (p < 0.001). With the proportion method DST results as reference standard, no statistically significant differences were observed in the sensitivity and specificity between iFIND and Xpert.ConclusionThe iFIND assay is a rapid and automated assay with sensitivity and specificity comparable to Xpert for early TB diagnosis and drug resistance screening, making it particularly suitable for implementation in primary healthcare settings and general hospitals.